PENDIDIKAN KARAKTER DALAM KOMIK GIGANA (DIGITAL MITIGASI BENCANA) GEMPA BUMI KARYA SITI ANAFIAH DAN SHANTA REZKITA - Anafiah, Siti; Rezkita, Shanta (Universitas Sarjanawiyata Tamansiswa, 2020)
The purpose of this study was to determine character education in the Gigana (Digital Disaster Mitigation) Comic Earthquake. This type of research is a qualitative descriptive study. This research uses the Abrams model pragmatic theory, which is the study of language usage that is associated with the context of its use. Data collection techniques namely refer, read, and note. Data analysis using Miles and Huberman consisting of data reduction, data display, and conclusion drawing and verification. The results of the study show that Comics as reading can benefit readers, namely children. Character education can be found in children's reading, one of them through comics. In the comic titled Comics Gigana (Digital Disaster Mitigation) Earthquakes by Siti Anafiah and Shanta Rezkita found 6 character values, namely peace, independence, responsibility, peace, environmental care, and social care. Such character education can be found through characters, characterizations, plot, settings, and mandates in the story.